Jan Mayen Island from surveys by the Austrian Polar-Year Expedition 1882-83 and the Imperial College Expedition 1938 - Royal Geographical Society (Great Britain) (Royal Geographical Society (Great Britain), 1939)
Relief shown by spot heights, shading and form lines. Accompanies article: Alexander King, J. N. Jennings: The Imperial College Expedition to Jan Mayen Island. The Geographical Journal, Vol. 94, No. 2 (Aug 1939), pp. 115-131. Color